Dalzanemdor (SAGE‐718), a novel, investigational N‐methyl‐D‐aspartate receptor positive allosteric modulator: Safety, tolerability, and clinical pharmacology in randomized dose‐finding studies in healthy participants and an open‐label study in participants with Huntington's disease - Aaron Koenig; Michael Lewis; Jeff Wald; Sigui Li; Mustafa Varoglu; Jing Dai; Abdul Sankoh; Katrina Paumier; James Doherty; Mike Quirk (Wiley, 2024)
Abstract N‐methyl‐D‐aspartate receptor (NMDAR)‐positive allosteric modulators (PAMs) represent a potential therapeutic strategy for cognitive impairment in disorders associated with NMDAR hypofunction, including Huntington's disease (HD) and Alzheimer's disease. Dalzanemdor (SAGE‐718) is a novel, investigational NMDAR PAM being evaluated for the potential treatment of cognitive impairment in these disorders. We report first‐in‐human, phase I, double‐blind, dose‐finding studies to assess the safety, tolerability, and clinical pharmacology of dalzanemdor. A single‐ascending dose study (dalzanemdor 0.35, 0.75, 1.5, or 3.0 mg vs. placebo) was conducted in healthy participants and included food effects. A multiple‐ascending dose study (14 days) was conducted in healthy participants (dalzanemdor 0.5 or 1.0 mg vs. placebo) and HD participants (open‐label dalzanemdor 1.0 mg) and included exploratory pharmacodynamics on cognitive performance. Dalzanemdor was generally well tolerated with no adverse events leading to discontinuation. Dalzanemdor exhibited pharmacokinetic parameters appropriate for once‐daily dosing. Following single and multiple doses in healthy participants, median terminal half‐life was 8-118 h, and the median time to reach maximum plasma concentration was 4-7 h. Exposures were dose‐proportional after single dose (6-46 ng/mL) and more than dose‐proportional after multiple doses (6-41 ng/mL). With multiple dosing, a steady state was achieved after 11 days in healthy participants and 13 days in HD participants. Dalzanemdor exposure decreased slightly with food. In HD participants, results suggest that dalzanemdor may improve cognitive performance on tests of executive function. These results support continued clinical development of dalzanemdor for the potential treatment of cognitive impairment in disorders of NMDAR hypofunction.